Efektivitas Pemanfaatan Publish or Perish Terhadap Pembelajaran Algoritma Pemrograman Pada Mahasiswa - Iramadhania , Fahira; Yahfizham (Journal Of Informatics And Busisnes, 2023)
Algorithm learning is related to computer programming, but that doesn't mean it always has to be about computer programming. An algorithm is a computer system with brainware, hardware and software that explains the stages of solving problems using a series of steps arranged systematically in a programming language. In the 21st century, programming has become a strategic skill and strength with all activities fulfilled by program devices such as laptops/pc, smartphones, and other sophisticated technology that is widely used in everyday life. The aim of writing this article is to determine the effectiveness of using Publish or Perish for students learning programming algorithms. By using a literature study method that utilizes the publish or perish application. Based on the discussion, the results showed that this application is very useful not only for students, but also for all academic circles, because the PoP application can be used to search for various sources of knowledge. The effectiveness of using the Publish or Perish application for students learning programming algorithms is also very effective and efficient, because it can improve the quality of learning and help shorten search time.